La perspective narrative dans les séries « Cop and Lab ». Quelles contributions aux représentations du monde scientifique et technique ? - Céline Nguyen; Marianne Chouteau; Eric Triquet; Catherine Bruguière (TV Series, 2012)
American series like The Experts and Bone have been met today with incontestable popular success. All while entertaining the views, these series place science and technology at the heart of their subjects: the action takes place in a scientific environment; the characters represent scientists; the story itself is carried by science and technology. If they do not attempt to be true or real, they work in the register of credibility. What representation of science and technology do these contemporary American series convey? How does the story related in each episode make use of science and technology to make a coherent and attractive fiction? Our goal is to show the mechanisms on which the links between science, technology, and the story are founded. To do this, we will follow two complementary lines of thought. The first aims to better understand the articulation between the police investigation at the heart of “Cop and doc shows” and scientific investigation. The second studies representations of science and technology that circulate and help construct the story. The comparative analysis of several episodes reveals the common and distinctive points between these two series and highlights different forms of interaction between science, technology, and the story. It also underlines the narratives potentialities of science and technology in this type of television production associated with entertainment.